Voltage Controller for Radial Distribution Networks with Distributed Generation - Kigen, Christopher; Abungu, Nicodemus Odero (International Journal of Scientific and Research Publications, 2014)
This paper presents a coordinated network controller whose objective is to maintain an optimal voltage profile across radial distribution networks with distributed generation. This is done by varying the output of the distributed generators. The controller was modeled as an optimization problem which was solved using Particle Swarm Optimization. The IEEE 33-bus and 69-bus test networks are then used to verify the effectiveness of the controller. The results obtained show that this controller can improve the voltage profile of a power network.
Keywords: Radial distribution networks; Particle swarm optimization; Modified backward-forward sweep